Design of Delivery NCC-Food Apps to Encourage Purchases of Nutrition Care Center Products - Santi, Maya Weka; Puspitasari, Trismayanti Dwi; Rachmawati, Ervina; Fitri, Zilvanhisna Emka; Ni’mah, Khomsatun; Yunus, Muhammad (Indonesian Journal Publisher, 2025)
Jember Regency was in the spotlight for the prevalence of stunted toddlers, reaching the highest rank in East Java with a figure of 34.9% in 2022. Teaching Factory Nutrition Care Center (NCC) has nutritional catering services with Managed Health Meal and Kids Meal packages. However, the ordering process was still done via telephone or chat from social media groups. The research objective was to generate an online application for Nutrition Care Center (NCC) called NCC-Food to encourage purchases of Nutrition Care Center products. It used the waterfall method, consisting of system investigation, system analysis, system design, system implementation, and system maintenance. Meanwhile, this article is limited to system design. The results showed that Delivery NCC Food Apps facilitates clients/patients to order nutritious food online according to nutritional adequacy rate needs, particularly for stunted toddlers. The research is expected to promote and improve the accessibility of healthy foods, in particular for stunted toddlers; therefore, the prevalence of stunting is expected to decrease significantly.